Changes in paediatric resuscitation knowledge among doctors. Issue 5 (1st May 2001) - Carapiet, D; Fraser, J; Wade, A; Buss, P W; Bingham, R
Abstract : AIMS: To investigate whether paediatricians have improved their resuscitation knowledge since 1992, and whether those who have attended a paediatric resuscitation course have greater knowledge than those who have not. METHODS: Telephone survey of 94 resident paediatricians admitting emergency cases. Questions on clinical scenarios were asked and adherence to internationally agreed guidelines in answering was determined. RESULTS: There were significantly more correct answers to 9/10 questions in 1999 compared to 1992. The 1999 doctors who had attended a course scored significantly better in 3/10 questions and achieved a higher total score (5.43 versus 4.55). CONCLUSIONS: Knowledge has improved since 1992; this has been over the period in which paediatric resuscitation courses were introduced. In 1999 those who had been on a course were more knowledgeable than those who had not.